Optimized volumetric modulated arc therapy versus 3D-CRT for early stage mediastinal Hodgkin Lymphoma without axillary involvement: a comparison of second cancers and heart disease risk - Filippi, Andrea Riccardo; Lohr, Frank (International journal of radiation oncology, biology, physics, 2015)
Purpose: The purpose of this study was to evaluate the risks of second cancers and cardiovascular diseases associated with an optimized volumetric modulated arc therapy (VMAT) planning solution in a selected cohort of stage I/II Hodgkin lymphoma (HL) patients treated with either involved-node or involved-site radiation therapy in comparison with 3-dimensional conformal radiation therapy (3D-CRT). Methods and Materials: Thirty-eight patients (13 males and 25 females) were included. Disease extent was mediastinum alone (n=8, 21.1%); mediastinum plus unilateral neck (n=19, 50%); mediastinum plus bilateral neck (n=11, 29.9%). Prescription dose was 30 Gy in 2-Gy fractions. Only 5 patients had mediastinal bulky disease at diagnosis (13.1%). Anteroposterior 3D-CRT was compared with a multiarc optimized VMAT solution. Lung, breast, and thyroid cancer risks were estimated by calculating a lifetime attributable risk (LAR), with a LAR ratio (LARVMAT-to-LAR3D-CRT) as a comparative measure. Cardiac toxicity risks were estimated by calculating absolute excess risk (AER). Results: The LAR ratio favored 3D-CRT for lung cancer induction risk in mediastinal alone (P=.004) and mediastinal plus unilateral neck (P=.02) presentations. LAR ratio for breast cancer was lower for VMAT in mediastinal plus bilateral neck presentations (P=.02), without differences for other sites. For thyroid cancer, no significant differences were observed, regardless of anatomical presentation. A significantly lower AER of cardiac (P=.038) and valvular diseases (P<.0001) was observed for VMAT regardless of disease extent. Conclusions: In a cohort of patients with favorable characteristics in terms of disease extent at diagnosis (large prevalence of nonbulky presentations without axillary involvement), optimized VMAT reduced heart disease risk with comparable risks of thyroid and breast cancer, with an increase in lung cancer induction probability. The results are however strongly influenced by the different anatomical presentations, supporting an individualized approach.